IMPLEMENTATION OF THE BLUE ECONOMY MISSION IN INDONESIA: ANALYSIS OF POTENTIAL, CONSTRAINTS, AND DEVELOPMENT DIRECTIONS - Julianto; Zainal Fatah; Eny Haryati (International Journal of Multidisciplinary Reseach, 2026)
Indonesia has enormous blue economy potential, but its contribution to the economy has not been optimal due to various implementation constraints. The main problem of this research is the gap between the potential of marine resources and the realization of their economic value at the regional level. This study aims to map the potential, identify obstacles, and formulate the direction of the blue economy mission development in Berau Regency, East Kalimantan. The research used a qualitative approach with a case study design. The research population was the actors involved in managing the Berau coastal blue economy, while the sample consisted of seven key informants selected purposively and snowball, including government officials, business actors, coastal communities, and academics. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña, which summarizes data, presents it, then draws and verifies conclusions, and tests its validity through triangulation. The results of the study revealed seven findings: large potential that has not automatically translated into local added value, fragmentation of cross-sector governance, multi-layered financing gaps, infrastructure and markets as determinants of income, ecological sustainability as an economic asset, the need to shift participation towards co-design, and the measurement of success that must be multidimensional. The study concluded that the implementation of the blue economy in Berau is systemic and thus requires institutional integration, strengthening of value chains and financing, protection of natural capital, and equitable participation, rather than stand-alone sectoral interventions.